(untitled) - Burton, Edward (Hoboko, New Jersey, 2016)
Drawing on his years of experience in counseling American business, in government as a diplomat living and working in Saudi Arabia, and as a businessman, Edward Burton introduces the reader to the emerging new class of entrepreneurs in the Kingdom of Saudi Arabia. The book tells the story of Saudi Arabia's boom and why it deserves more of the world's attention from a global business perspective. Much of the book's content focuses on the transformative effects the aging of its family-owned business leaders are having on the reshaping of corporate boards, influencing technological innovation and changing the way business is done in what is one of the world's youngest and wealthiest countries. The book answers the question why Saudi Arabia's current industrial and economic boom has relevance to global business and why it is important to American competitiveness to better know and understand Saudi Arabia. This book is important for investors also because of the following facts about Saudi Arabia
Keywords: Đầu tư, nước ngoài,Investments, foreign; Ả Rập Saudi,Saudi Arabia